Diseño de un módulo didáctico para la medición y control de nivel, presión y caudal para un laboratorio de automatización (2019)
For the development of the project initially, was made a diagnostic of different components present in the instrumentation and process control laboratory that were considered could be useful for the development of the didactic module, after this, the different necessary parameters and requirements for the development of the module were established and decide about the components evaluated They were in good condition. Next step, an evaluation process was carried out to the different alternatives for the measurement of the three physical variables controlled in the module, which gave way to the next phase which consisted in the design of the different systems of the module and the selection of necessary components for its correct operation. Once the design and components that would be part of the module were defined, the corresponding control system design for the equipment was carried out (in such a way that it was compatible with a data acquisition card and a programmable logic controller (PLC)) Additionally, drawings of the equipment, maintenance and inspection manual, operation manual, and laboratory guides were made. Finally, an analysis of the environmental impact that the module would generate and an analysis of project costs was performed.